48. Rubrics and Exemplars in Text-Conferencing - Zahara, Allan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
The author draws on his K-12 teaching experiences in analyzing the strengths and weaknesses of asynchronous, text-based conferencing in online education. Issues relating to Web-based versus client-driven systems in computer-mediated conferencing (CMC) are examined. The paper also discusses pedagogical and administrative implications of choosing a synchronous conferencing approach.